2018
DOI: 10.1186/s41935-018-0078-2
|View full text |Cite
|
Sign up to set email alerts
|

Postmortem computed tomography and autopsy for detection of lesions and causes of death in gunshot injury cases: a comparative study

Abstract: Background: Firearm injuries are a common cause of death in cases typically investigated by medical examiners. Postmortem multislice computed tomography (PMCT) provides valuable information that enhances the autopsy examination. This study was conducted to compare PMCT and autopsy for the detection of injuries and causes of death in cases of fatal firearm injuries. Thirty cadavers were scanned with PMCT and then underwent autopsy. The results of the two techniques were compared regarding entry wounds, wound ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The visualisation and analysis of post-mortem specimens have been completely transformed by the incorporation of advanced imaging technologies, including multispectral imaging, three-dimensional (3D) imaging, and sophisticated microscopy techniques. In a study conducted by Shereen Ahmad et.al mentioned about the Postmortem multislice computed tomography (PMCT) technique for autopsies which is a Modern imaging technology and a non-invasive technique which provide forensic pathology experts to improved clarity and accuracy by visualising microscopic tissue structures, lesions, cellular abnormalities, and wound path visualisation in high-resolution and detail [16]. These cutting-edge imaging technologies enable forensic pathologists to perform exhaustive and comprehensive analyses, making it easier to precisely identify and document important forensic evidence and pathological findings.…”
Section: Advanced Imaging Technologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The visualisation and analysis of post-mortem specimens have been completely transformed by the incorporation of advanced imaging technologies, including multispectral imaging, three-dimensional (3D) imaging, and sophisticated microscopy techniques. In a study conducted by Shereen Ahmad et.al mentioned about the Postmortem multislice computed tomography (PMCT) technique for autopsies which is a Modern imaging technology and a non-invasive technique which provide forensic pathology experts to improved clarity and accuracy by visualising microscopic tissue structures, lesions, cellular abnormalities, and wound path visualisation in high-resolution and detail [16]. These cutting-edge imaging technologies enable forensic pathologists to perform exhaustive and comprehensive analyses, making it easier to precisely identify and document important forensic evidence and pathological findings.…”
Section: Advanced Imaging Technologiesmentioning
confidence: 99%
“…These cutting-edge imaging technologies enable forensic pathologists to perform exhaustive and comprehensive analyses, making it easier to precisely identify and document important forensic evidence and pathological findings. PMCT can be used as a post-mortem alternative or as an autopsy complement to capture multidimensional data and produce accurate anatomical reconstructions (Figure 1) [16].…”
Section: Advanced Imaging Technologiesmentioning
confidence: 99%
“…Recently, several studies have proposed the use of PMCT to determine the cause of death [1][2][3][4][5][6][7][8][9][10]. The PMCT is considered the most feasible imaging modality because it is widely available.…”
Section: Case Historymentioning
confidence: 99%
“…The hyperattenuation of blood clot or hematoma can be easily visualized in conventional methods and PMCT. Elkhateeb et al [7] reported that PMCT was as valuable as autopsy for detecting the direction of firing and internal bleeding of gunshot injuries.…”
Section: Case Historymentioning
confidence: 99%